Dietary phosphorus intake modifies the association between total cholesterol and lumbar spine bone mineral density: results from NHANES 2011–2016 - Yu, Dechen; Li, Pan; Su, Kangkang; Cao, Xiongfei; Yu, Xiaolei; Ye, Zhengxu; Li, Mo (Frontiers in Nutrition, 2025)
BackgroundThe connection between total cholesterol (TC) and lumbar spine bone mineral density (BMD) is well-documented, yet the role of dietary phosphorus intake in this relationship is not fully understood. This cross-sectional study aims to explore how dietary phosphorus affects the link between TC and lumbar spine BMD.MethodsData from the National Health and Nutrition Examination Survey (NHANES) spanning 2011 to 2016 were analyzed, involving 7,155 participants. Based on the median daily phosphorus intake, participants were divided into a low phosphorus intake group (phosphorus intake <1,445 mg/d) and a high phosphorus intake group (phosphorus intake ≥ 1,445 mg/d). A multiple linear regression analysis was performed to investigate the association between TC and lumbar spine BMD, with a focus on determining if dietary phosphorus intake may serve as a potential influencing factor.ResultsThe study revealed a negative association between TC and lumbar spine BMD. The strength of this relationship varied between the low and high phosphorus intake groups, with β values of −0.219 (95% CI: −0.334 to −0.105) for the low group and − 0.420 (95% CI: −0.548 to −0.291) for the high group. Additionally, there was an interaction between total cholesterol and dietary phosphorus intake in reducing lumbar spine bone density (P for interaction = 0.0168).ConclusionOur study results indicate that dietary phosphorus intake influences the relationship between TC and lumbar spine BMD, which may have important implications for clinical management.